Post-transcriptional regulatory crosstalk between micrornas and canonical TGF-β/BMP signalling cascades on osteoblast lineage: a comprehensive review - Loh, Hui-Yi; Norman, Brendan P.; Lai, Kok-Song; Cheng, Wan-Hee; Nik Abd. Rahman, Nik Mohd Afizan; Mohamed Alitheen, Noorjahan Banu; Osman, Mohd Azuraidi (MDPI, 2023)
MicroRNAs (miRNAs) are a family of small, single-stranded, and non-protein coding RNAs about 19 to 22 nucleotides in length, that have been reported to have important roles in the control of bone development. MiRNAs have a strong influence on osteoblast differentiation through stages of lineage commitment and maturation, as well as via controlling the activities of osteogenic signal transduction pathways. Generally, miRNAs may modulate cell stemness, proliferation, differentiation, and apoptosis by binding the 3′-untranslated regions (3′-UTRs) of the target genes, which then can subsequently undergo messenger RNA (mRNA) degradation or protein translational repression. MiRNAs manage the gene expression in osteogenic differentiation by regulating multiple signalling cascades and essential transcription factors, including the transforming growth factor-beta (TGF-β)/bone morphogenic protein (BMP), Wingless/Int-1(Wnt)/β-catenin, Notch, and Hedgehog signalling pathways; the Runt-related transcription factor 2 (RUNX2); and osterix (Osx). This shows that miRNAs are essential in regulating diverse osteoblast cell functions. TGF-βs and BMPs transduce signals and exert diverse functions in osteoblastogenesis, skeletal development and bone formation, bone homeostasis, and diseases. Herein, we highlighted the current state of in vitro and in vivo research describing miRNA regulation on the canonical TGF-β/BMP signalling, their effects on osteoblast linage, and understand their mechanism of action for the development of possible therapeutics. In this review, particular attention and comprehensive database searches are focused on related works published between the years 2000 to 2022, using the resources from PubMed, Google Scholar, Scopus, and Web of Science.